Evaluation of the anti-biofilm activities of bacterial cellulose-tannic acid-magnesium chloride composites using an in vitro multispecies biofilm model. Issue 6 (5th October 2021) - He, Wei; Zhang, Zhaoyu; Chen, Jing; Zheng, Yudong; Xie, Yajie; Liu, Wenbo; Wu, Jian; Mosselhy, Dina A
Abstract: Chronic wounds are a serious worldwide problem, which are often accompanied by wound infections. In this study, bacterial cellulose (BC)-based composites introduced with tannic acid (TA) and magnesium chloride (BC-TA-Mg) were fabricated for anti-biofilm activities. The prepared composites' surface properties, mechanical capacity, thermal stability, water absorption and retention property, releasing behavior, anti-biofilm activities and potential cytotoxicity were tested. Results showed that TA and MgCl2 particles closely adhered to the nanofibers of BC membranes, thus increasing surface roughness and hydrophobicity of the membranes. While the introduction of TA and MgCl2 did not influence the transparency of the membranes, making it beneficial for wound inspection. BC-TA and BC-TA-Mg composites displayed increased tensile strength and elongation at break compared to pure BC. Moreover, BC-TA-Mg exhibited higher water absorption and retention capacity than BC and BC-TA, suitable for the absorption of wound exudates. BC-TA-Mg demonstrated controlled release of TA and good inhibitory effect on both singly cultured Staphylococcus aureus and Pseudomonas aeruginosa biofilm and co-cultured biofilm of S. aureus and P. aeruginosa . Furthermore, the cytotoxicity grade of BC-TA-6Mg membrane was eligible based on standard toxicity classifications. These indicated that BC-TA-Mg is potential to be used as wound dressings combating biofilms in chronic wounds.